The Influence of Accountability and Transparency of Fund Management on Village Government Trust in The Paguyangan Sub-District of Brebes - Putria Wati Nur Arum; Selamet Eko Budi Santoso; Eko Hariyanto; Hardiyanto Wibowo (Jurnal Indonesia Sosial Teknologi, 2024)
Study This aims To analyze the influence of accountability and transparency in village fund management to level the trust public in government villages in the District Paguyangan. Primary data was obtained through a spread questionnaire to 125 respondents from 8 villages in the District Selected community​ using a purposive sampling technique. Amount sample the considered representative For describing population research totalling 12 villages.​ The research method used​ is an approach quantitative with analysis of multiple linear regression. The data analysis process includes instrument testing (validity and reliability), assumption testing classical (normality, heteroscedasticity, multicollinearity), and hypothesis testing using the SPSS application. Research results show that accountability and transparency in village fund management are influential and significant to the enhancement trust public in government villages. The more accountability and transparency in managing village funds, the level of trust public will the more tall.